Teachers’ TPACK in Teaching EFL during Covid-19 Pandemic - Feny Martina; Zelvia Liska Afriani; Septian Aryani (Linguists : Journal Of Linguistics and Language Teaching, 2022)
This study explores the TPACK of EFL teachers in two distinct school districts during the Covid-19 pandemic. This study comprised two English teachers from rural and urban schools in Bengkulu, Indonesia, with 2 to 10 years of experience teaching English. The researchers collected the data utilizing an interview-based comparative descriptive methodology to address research questions. Following the interview, the collected data was transcribed. The findings of this study indicate that urban teachers have a higher level of TPACK than rural teachers in terms of their ability to use technology and manage classes when teaching English during the Covid-19 pandemic, particularly concerning online learning applications such as Zoom meetings, WhatsApp, Google Classroom, and the YouTube app. On the other hand, rural EFL teachers have insufficient TPACK. Due to a lack of time to design technology lesson plans, technology training, and inadequate supporting facilities and infrastructure, such as limited internet network availability and power outages, teachers lack knowledge of technological advances for online learning. Even though teachers in rural and urban areas had never utilized an online learning system during the previous school year, they had varying capacities for addressing problems that developed while utilizing this system.